A RANS approach for transfer function plot based on discrete fourier transform. (4th May 2022) - Cakici, Ferdi; Kahramanoglu, Emre
ABSTRACT: Besides the other hydrodynamic phenomena, the ship design process includes also the accurate prediction of the motions in waves. In this paper, a Discrete Fourier Transform (DFT) based method is presented for calculations of ship motion transfer functions (TFs) by using Reynolds Averaged Navier Stokes (RANS) approach. The DTMB 5512 hull form is selected for the proof of the accuracy of the proposed method at the Froude number of 0.41 and head waves. Instead of sending regular waves separately to the model ship in a virtual towing tank, a wave energy spectrum is defined and the created long-crested irregular wave system is sent to the model ship. With the aid of the DFT technique, irregular vertical ship motions in the time domain are transformed into the frequency domain. With the proposed RANS method, it is reported that CPU time spent for CFD analyses are significantly dropped compared to traditional RANS TFs calculation processes.